The daily and policy-relevant liquidity effects - Daniel L. Thornton (European Central Bank (ECB), 2008)
The phrase “liquidity effect” was introduced by Milton Friedman (1969) to describe the first of three effects on interest rates caused by an exogenous change in the money supply. The lack of empirical support for the liquidity effect using monthly and quarterly data using various monetary and reserve aggregates led Hamilton (1997) to suggest that more convincing evidence of the liquidity effect could be obtained using daily data – the daily liquidity effect. This paper investigates the implications of the daily liquidity effect for Friedman's liquidity effect using a comprehensive model of the Fed's daily operating procedure. The evidence indicates that it is no easier to find convincing evidence of a Friedman's liquidity effect using daily data than it has been using lower frequency data.
Keywords: E40; E52; 330; federal funds rate; FOMC; liquidity effect; monetary policy; operating procedure; Liquiditätseffekt; Geldmengensteuerung; Theorie; USA